PENGEMBANGAN MODEL PROBLEM BASED LEARNING BERBASIS ETNOMATEMATIKA DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN BERPIKIR KREATIF SISWA - Alkausar Saragih, Bambang Hermanto, Saiful Bahri, Samsul Bahri, (JURNAL ILMU PENDIDIKAN, 2025)
To improve students' problem-solving skills, the teaching and learning process must be carried out. This is very important for mathematics teachers because students with low problem-solving skills will find it difficult to process concepts and solve the problems given by the teacher. Based on the researcher's experience such as internships or teaching at schools, the main problem faced To solve this problem, teachers must use innovative and creative learning approaches that help students understand the lessons and apply them in everyday life. Understanding the problem, making a solution plan, implementing the solution plan, and reviewing all the steps that have been taken are all part of the students' ability to solve mathematical problems (Dea Aurelya Nasution et al.,/1023). To solve this problem, the researcher used the Problem Based Learning (PBL) model, one of the learning models recommended by teachers and proven to be effective. From the results of the research and discussion on the development of teaching materials using the Problem Based Learning model based on ethnomathematics for the topic of flat-sided space figures on cubes and cuboids in class IX at SMA Negeri 2 Lubuk Pakam. It can be concluded that the teaching materials for flat-sided space figures on cubes and rectangular prisms based on ethnomathematics that were developed are valid, practical, and effective.